A morphological and molecular review of the genus Goniurosaurus, including an identification key - Ngo, Hai Ngoc; Nguyen, Huy Quoc; Tran, Hieu Minh; Ngo, Hanh Thi; Le, Minh Duc; Gewiss, Laurenz Rafael; van Schingen-Khan, Mona; Nguyen, Truong Quang; Ziegler, Thomas (European Journal of Taxonomy, 2021)
The genus Goniurosaurus (tiger geckos) currently consists of 23 species distributed in China, Japan and Vietnam. Several species complexes and recent discoveries of cryptic species pose challenges to the species identification, which is crucial to effectively implement the recent listing of the species from China and Vietnam in CITES Appendix II and the species from Japan in CITES Appendix III. Based on the results of our field work in northern Vietnam and data compiled from literature, we herein provide a taxonomic review of the genus Goniurosaurus. Our phylogenetic analyses showed that all recorded populations of tiger geckos from Vietnam, which were found to be monophyletic with low intra-specific genetic divergences, are assigned to one of the four species: G. catbaensis, G. huuliensis, G. lichtenfelderi or G. luii. Both genetic and morphological analyses confirm that the species from China and Vietnam can be split into three major groups. Based on the newly collected data, we provide an extended morphological description of the Vietnamese species. In addition, we provide an identification key for all Goniurosaurus species from China, Japan and Vietnam in order to assist authorities in the enforcement of the recent CITES listing.